El indio entre naturaleza y urbanidad: representaciones sociales y literarias - Rivera G, Pamela R. A. (2020)
I propose to delve into the study of the poetry of Jesús Ramón Vera by tracing a literary (Kaliman, 1993) and cultural region in dialogue with the Andean region (Palermo - Altuna, 1996). I will take poems from Bermejo (1993), COM.PAR.SA (2001) and Nobody se crosses de bando (2010) and I will integrate indigenous spaces and knowledge, both Andean and from the original communities of the Chaco. The Indian figurations that I will explore will be constituted in language (enunciation) and from the performative presence of bodies in spaces. Finally, I will show how the thought of these cultures is transferred with these migrant subjects (Cornejo Polar, 1996) to the current cities where the urban Indian becomes a nomadic subject.